Nonlinear Jordan Higher Derivations of Triangular Algebras (Communications in Mathematical Research, 2021)
In this paper, we prove that any nonlinear Jordan higher derivation ontriangular algebras is an additive higher derivation. As a byproduct, we obtain thatany nonlinear Jordan derivation on nest algebras over infinite dimensional Hilbertspaces is inner.